2017
DOI: 10.3389/fnhum.2017.00134
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Mechanisms of Tongue Sensorimotor Functions in Humans: A Review of the Magnetoencephalography Approach

Abstract: The tongue plays important roles in a variety of critical human oral functions, including speech production, swallowing, mastication and respiration. These sophisticated tongue movements are in part finely regulated by cortical entrainment. Many studies have examined sensorimotor processing in the limbs using magnetoencephalography (MEG), which has high spatiotemporal resolution. Such studies have employed multiple methods of analysis, including somatosensory evoked fields (SEFs), movement-related cortical fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 118 publications
1
8
0
Order By: Relevance
“…We have found that the significant CMC existed in all nine channels covering the lateral and medial parts of the sensorimotor area in theta, alpha, and beta frequency bands in accordance with the previous works (Maezawa et al, 2014(Maezawa et al, , 2016Maezawa, 2017). For the finger muscles, CMC was not consistently observed in the theta and alpha frequency bands (Mima and Hallett, 1999).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We have found that the significant CMC existed in all nine channels covering the lateral and medial parts of the sensorimotor area in theta, alpha, and beta frequency bands in accordance with the previous works (Maezawa et al, 2014(Maezawa et al, , 2016Maezawa, 2017). For the finger muscles, CMC was not consistently observed in the theta and alpha frequency bands (Mima and Hallett, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Transcranial magnetic stimulation (TMS) works showed changes in corticomotoneuronal activities by the evaluation of motor-evoked potentials in the pharyngeal muscles in the resting state after repetitive TMS, which increased the cortical excitability of the stimulated area (Michou et al, 2014). In the previous works using MEG, significant CMCs in theta, alpha, and beta frequency bands have been found during tongue protrusion task, which suggests that cortical motor commands can be evaluated in oral apparatus by CMC (Maezawa et al, 2014(Maezawa et al, , 2016Maezawa, 2017). Although it is important to evaluate the corticomotoneuronal activities during swallow movements with activated submental group muscles and pharyngeal muscles (Ding et al, 2002), there has been no analogous work on them.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Alexander B. Remsik et al [40] did a randomized controlled trial on 21 cerebrovascular accident patients with persistent upper extremity impairment. They received a maximum of 18-30 hours of therapeutic interventions with novel electroencephalogram-based brain computer interface driven functional electrical stimulation device (EEG -BCI -FES).…”
Section: Tongue Stimulation In Stroke Patientsmentioning
confidence: 99%
“…Conventional CKC methods quantify the coupling between magnetoencephalographic (MEG) signals and finger kinematics, which are measured using an accelerometer (ACC) during repetitive, rhythmic, and voluntary finger movements (Bourguignon et al, 2011;. Previous studies have shown that the CKC mainly reflects the proprioceptive input into the SM1 (Piitulainen et al, 2013a;Bourguignon et al, 2015;2017); this feature is comparable to the strongest deflections observed in the cortical movement evoked fields (MEFs) associated with voluntary finger movements (Cheyne et al, 1989;Gerloff et al, 1998). However, it is difficult to apply this technique to regions of the tongue using an ACC because the ACC produces excessive magnetic artifacts, which easily contaminate the cortical magnetic activity due to the short distance between the tongue and MEG sensors.…”
Section: Introductionmentioning
confidence: 99%